As dimensões do capital psicológico no comportamento empreendedor: um estudo em micro e pequenos empreendedores cearenses do setor de serviços - Lima, Danielle Luz (2023)
Psychological capital is the positive state that is characterized by having confidence in oneself (self-efficacy), making a positive attribution (optimism) about succeeding, remaining persevering (hope) and having resilience to achieve the success one seeks. Entrepreneurial behavior can be understood as particular characteristics that are repeated in the face of some opportunities in which the entrepreneur perceives, acts and thinks in an entrepreneurial way. In this context, Positive Psychology research emerges by deepening the study of the positive aspects of people and a more meaningful life with greater well-being. In view of this, the Entrepreneurial Behavior construct notes the exploration in its practices of how psychological capital and the application of the terms self-efficacy, optimism, resilience and hope (dimensions of Psychological Capital) collaborate with a more positive approach in the work context. In this scenario, the general objective of this study is to analyze how the dimensions of Psychological Capital are characterized by Entrepreneurial Behavior. The specific objectives are 1) Explore the notions and perception that entrepreneurs have regarding the 4 dimensions of Psychological Capital; 2) Investigate entrepreneurs' cognitions about entrepreneurial behavior; 3) Identify the association between entrepreneurial behaviors with the 4 dimensions of Psychological Capital and 4) Describe how, from the perspective of entrepreneurs, these 4 dimensions and entrepreneurial behaviors are present in their practices. As for the methodological procedures, this is a qualitative investigation. To this end, semi-structured interviews were conducted with 12 entrepreneurs, appointed by an association of entrepreneurs. The interview script was conducted both in person and online, suggested with participation by adhesion. The interview script was prepared and applied based on the Reflective Cognitive Approach, using the card technique. Data analysis was done through content analysis and presentation of results will be demonstrated in mind maps using MindManager software. The results pointed to a diversity of data in which each entrepreneur imprinted their conceptions of entrepreneurial behavior based directly on their daily practices, such as acting repeatedly or changing strategies to achieve their goals, in addition to taking personal responsibility for the performance of their company and, furthermore, putting yourself in situations that involve challenges or moderate risks. The results revealed that the 4 dimensions of Psychological Capital are closely linked and communicate with the Characteristics of Entrepreneurial Behavior (ECB), bringing effective contributions to the assertiveness of their decisions and understanding the relevance of maintaining or improving their behaviors related to setting goals, demand for quality and effectiveness and independence and self-confidence. As contributions to the entrepreneur's practice, this study provides relevant information for the study of entrepreneurial behavior through the presentation of the meaning of Psychological Capital in the view of entrepreneurs and which of these behaviors most encourage the creation of strategies and continuous improvement of being an entrepreneur. Based on this study, it is possible to invest in action planning to remodel the most relevant practices in order to become an increasingly assertive entrepreneur that brings better results.